Law Student Views on the Principles of Legal Research Website: An User Experience Study - Intahchomphoo, Channarong; Jeske, Margo; Landriault, Emily (Université d'Ottawa | University of Ottawa, 2016)
The Principles of Legal Research Website of the University of Ottawa’s Brian Dickson Law Library is a bilingual (English and French) online learning tool for all first year students in both Common Law and Civil Law. 1 Law librarians apply this e-learning website to facilitate teaching components such as student assignments, and assessments. This user experience study aims to investigate law students’ real experience with the system. Their feedback will be used for future development planning as well as analysing user behaviour trends. The authors investigate the following aspects: accuracy of information, interface design, navigation system, Web 2.0, social media, and smartphone version.
Keywords: User experience study; E-learning website; Human-Computer Interaction